Water accounting to assess use and productivity of water: evolution of a concept and new frontiers. - Karimi, P.; Molden, David J.; Bastiaanssen, Wim G.M.; Xueliang Cai (Edward Elgar Publishing, 2012)
Coping with water scarcity requires improvement in the way that water is managed in most areas of the world. Underpinning water management is the basic information on the availability and use of water resources. However, reliable information about water resources is hard to obtain for several reasons, one of which is availability of data. Even where data are available the task of identifying who uses how much water remains difficult because of hydrologic complexities of water use, storage and water reuse, especially in heavily developed river basins. The objective of the chapter is to introduce the International Water Management Institute (IWMI) Water Accounting Framework (IWMI WA), developed in 1997, and recent developments related to this water accounting system. IWMI WA provides information on supply and use of water and relates water use to the economy. It is a multiscale method to account for the amount of water available, how much is used by various sectors and the value derived from the use to promote understanding of water use and assist with improved water management. In illustrating the IWMI WA system, concepts and definitions plus examples from different areas and scales are discussed in this chapter. In a basin context, water accounting defines water availability and helps users to understand water use and benefits and costs derived from its use.